АБУЛ БАРАКОТ НАСАФИЙНИНГ “КАНЗУДДАҚОИҚ” АСАРИ ҲАНАФИЙ МАЗҲАБИДАГИ МЎЪТАБАР ФИҚҲИЙ МАТНЛАРДАН БИРИДИР - Жўраев, Ф. (SCIENCE and SOCIETY, 2019)
The author of the article emphasizes that the work “Kanzud-Daqaiq” is one of the original and short texts of fiqh in Khanafi Madhab, and students can get large amount of information for a short time from it.
Keywords: jurisprudence; law; legal doctrine; hanafi; text; short; hardworking; detailed; explain; treasure; education; flour; work; question; the rights; cause; evidence; the imam